2008 3rd IEEE International Workshop on Horizontal Interactive Human Computer Systems 2008
DOI: 10.1109/tabletop.2008.4660190
|View full text |Cite
|
Sign up to set email alerts
|

Little fingers on the tabletop: A usability evaluation in the kindergarten

Abstract: This paper presents selected results from an experimental study designed to compare fantasy play in a virtual and physical setting. Twenty-two children (aged 3 and 4) played in same-sex dyads with a real wooden tree house and its virtual implementation on a DiamondTouch tabletop. The study evinced several problems in the interaction with the tabletop as children often struggled to drag the objects displayed on the surface. An error analysis is presented and results are used to propose guidelines for improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 5 publications
1
26
0
Order By: Relevance
“…This is in contrast to the more varied types of finger interactions and manipulation in our study. Our study findings compare more closely to those of Mansor et al [6] who showed that young children (aged 3-4 years old) utilised thumb and middle finger, speculating that such interaction technique helped objects stick easily on the young children's fingers leading to better movement on the digital object. It is therefore possible that using the thumb, middle and little fingers are types of object interaction technique exhibited by children who: 1) are new to interactive table and encountered it for the very first time, and 2) wanted to leverage the usage of other fingers (apart from the index finger) to aid with the movement of the digital objects.…”
Section: Multi-finger Touch Techniquesupporting
confidence: 89%
See 1 more Smart Citation
“…This is in contrast to the more varied types of finger interactions and manipulation in our study. Our study findings compare more closely to those of Mansor et al [6] who showed that young children (aged 3-4 years old) utilised thumb and middle finger, speculating that such interaction technique helped objects stick easily on the young children's fingers leading to better movement on the digital object. It is therefore possible that using the thumb, middle and little fingers are types of object interaction technique exhibited by children who: 1) are new to interactive table and encountered it for the very first time, and 2) wanted to leverage the usage of other fingers (apart from the index finger) to aid with the movement of the digital objects.…”
Section: Multi-finger Touch Techniquesupporting
confidence: 89%
“…Many of the studies surrounding children and multitouch tabletops are based on participants from the Western world (e.g. Mansor [6] and Harris et al [3]) but we have very little understanding on how children in other countries and cultural settings interact with digital objects, such as those on interactive tables. Within these settings, there may be different social protocols determining how task-based collaboration is organised and mediated through conversation, interaction and arrangement of artefacts.…”
Section: Introductionmentioning
confidence: 99%
“…This inherent ability of touch systems to engage children's attention is being widely exploited to promote learning activities from pre-kindergarteners to adolescents [12,18,11]. Moreover, some studies have demonstrated that the technology can also be used to promote collaboration between peers [16,17,7] and to foster creativity [8,2].…”
Section: Related Workmentioning
confidence: 99%
“…Overall, cases where identifying finger orientation is erroneous rarely occur. For instance, if a finger approaches the surface from a steep or even perpendicular angle [11,16], the near proximity of the contact area often does not consist of sufficient finger or hand pixels. Another situation appears when finger contacts of different hands are placed too close together.…”
Section: Finger Position and Orientationmentioning
confidence: 99%